Pengaruh Motivasi Kerja Dan Beban Kerja Terhadap Turnover Karyawan (sales) di PT Setiajaya Mobilindo - ibnia zahra, nuriza; Utomo, Wahyudi; Purniwarti, Titik; Mubarak, Fauzi; Onida, Mawar (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2024)
PT Setiajaya Mobilindo, a company in the automotive industry operating under Toyota Astra Motor (TAM), specializes in selling Toyota vehicles. This study explores the impact of work motivation and workload on employee turnover at PT Setiajaya Mobilindo. Utilizing a quantitative research approach, the study surveyed 70 former sales employees of the company. Data analysis was conducted using the Smart PLS method. The findings reveal that the statistical value for work motivation is 2.301, which exceeds the t-table value of 1.96, with a p-value of 0.021, indicating significance below the 0.05 threshold. For the workload variable, the t-statistic is 4.444, surpassing the t-table value of 1.96, and the p-value is 0.000, also below 0.05. The R-Square value of 0.694 indicates that 69.4% of the variance in turnover is explained by work motivation and workload, while the remaining 30.6% is attributed to other factors not covered by this study. Thus, both work motivation and workload significantly affect turnover.